Regulation of Marginal Zone B-Cell Differentiation by MicroRNA-146a - King, Jennifer K.; Ung, Nolan M.; Paing, May H.; Contreras, Jorge R.; Alberti, Michael O.; Fernando, Thilini R.; Zhang, Kelvin; Pellegrini, Matteo; Rao, Dinesh S. (Frontiers in Immunology, 2017)
B-cell development in the bone marrow is followed by specification into functional subsets in the spleen, including marginal zone (MZ) B-cells. MZ B-cells are classically characterized by T-independent antigenic responses and require the elaboration of distinct gene expression programs for development. Given their role in gene regulation, it is not surprising that microRNAs (miRNAs) are important factors in B-cell development. Recent work demonstrated that deficiency of the NFκB feedback regulator, miR-146a, led to a range of hematopoietic phenotypes, but B-cell phenotypes have not been extensively characterized. Here, we found that miR-146a deficient mice demonstrate a reduction in MZ B-cells, likely from a developmental block. Utilizing high-throughput sequencing and comparative analysis of developmental stage-specific transcriptomes, we determined that MZ cell differentiation was impaired due to decreases in Notch2 signaling. Our studies reveal miR-146a-dependent B-cell phenotypes, and highlight the complex role of miR-146a in the hematopoietic system.